2018
DOI: 10.1136/bjophthalmol-2017-311390
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering of retina and Bruch’s membrane: a review of cells, materials and processes

Abstract: The biological, structural and functional configuration of Bruch's membrane (BM) is significantly relevant to age-related macular degeneration (AMD) and other chorioretinal diseases, and AMD is one of the leading causes of blindness in the elderly worldwide. The configuration may worsen along with the ageing of retinal pigment epithelium and BM that finally leads to AMD. Thus, the scaffold-based tissue-engineered retina provides an innovative alternative for retinal tissue repair. The cell and material require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Future research should also investigate the use of scaffolds as dual-purpose platforms, to both regenerate cells and deliver drugs and biologics to target ocular tissues. PCL Synthetic Biocompatible; nontoxic; low cost; elastic, easy pore size and shape control; slow degradation rate (24 and 48 months); PCL nanofibrous scaffolds prepared by electrospinning; scaffold with high surface-to-volume ratio; high porosity (85%); high pore interconnectivity; sufficient tensile strength; promoted cell proliferation; scaffolds prepared by electrospinning with smaller pore size; PCL fiber orientation similar to native collagen; scaffolds prepared by electrospinning with average pore size 13.3±5.5 mm and thickness 114±16 mm maintaining high cell viability; similar fiber orientation to native collagen in ECM; pore size: 1.2 m; promote cell attachment and proliferation; nanofibrous scaffold of PCL and gelatin with lower cytotoxicity [48,61,68,109,110] PCL-treated plasma Synthetic Biocompatible; convenient; cost-effective; nanofibrous scaffolds prepared by electrospinning with porous structure, good cell adhesion and proliferation [110] PLGA Synthetic FDA approved;, biodegradable; biocompatible;, tailored degradation time; limited flexibility; degrade within weeks; scaffold prepared by electrospinning technique with pore size of 10.4±6.2 mm and thickness of 109±17 mm maintained high cell viability and preserved human corneal epithelial cell morphology; scaffold of PLLA and PLGA; high degree of porosity; uniform pore structure; controllable configurations and thickness; poor flexibility; caused inflammatory, fibrosis and foreign body responses; bulk degradation resulted in non-uniform release profile [66,93] PLDLA Synthetic Hydrophilic; similar mechanical properties to PLC with shorter degradation time; scaffolds with relatively high membrane porosity with surface coating to mimic collagen on BrM; enhance interaction with cells and tissues [111] PMMA Synthetic No foreign body response; limitations to supporting cell growth; toxic; nondegradable; scaffolds prepared by electrospinning with pore size diameter of 26.8±17.5 mm and thickness of 150±12 mm; lowest viscosity resulted in thickest fibers, largest interstitial spaces, thickest scaffolds, and best light transmission [65,66] Parylene-C Synthetic Biocompatible; nontoxic; good mechanical strength and biostability; semipermeable to macromolecules when thickness reduced to submicron range; mesh-supported submicron membrane; can withstand significant stretching force; epithelial-like morphology; tight intracellular junctions; correct polarization; well-developed microvilli; good cell adherence [112] A C C E P T E D M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research should also investigate the use of scaffolds as dual-purpose platforms, to both regenerate cells and deliver drugs and biologics to target ocular tissues. PCL Synthetic Biocompatible; nontoxic; low cost; elastic, easy pore size and shape control; slow degradation rate (24 and 48 months); PCL nanofibrous scaffolds prepared by electrospinning; scaffold with high surface-to-volume ratio; high porosity (85%); high pore interconnectivity; sufficient tensile strength; promoted cell proliferation; scaffolds prepared by electrospinning with smaller pore size; PCL fiber orientation similar to native collagen; scaffolds prepared by electrospinning with average pore size 13.3±5.5 mm and thickness 114±16 mm maintaining high cell viability; similar fiber orientation to native collagen in ECM; pore size: 1.2 m; promote cell attachment and proliferation; nanofibrous scaffold of PCL and gelatin with lower cytotoxicity [48,61,68,109,110] PCL-treated plasma Synthetic Biocompatible; convenient; cost-effective; nanofibrous scaffolds prepared by electrospinning with porous structure, good cell adhesion and proliferation [110] PLGA Synthetic FDA approved;, biodegradable; biocompatible;, tailored degradation time; limited flexibility; degrade within weeks; scaffold prepared by electrospinning technique with pore size of 10.4±6.2 mm and thickness of 109±17 mm maintained high cell viability and preserved human corneal epithelial cell morphology; scaffold of PLLA and PLGA; high degree of porosity; uniform pore structure; controllable configurations and thickness; poor flexibility; caused inflammatory, fibrosis and foreign body responses; bulk degradation resulted in non-uniform release profile [66,93] PLDLA Synthetic Hydrophilic; similar mechanical properties to PLC with shorter degradation time; scaffolds with relatively high membrane porosity with surface coating to mimic collagen on BrM; enhance interaction with cells and tissues [111] PMMA Synthetic No foreign body response; limitations to supporting cell growth; toxic; nondegradable; scaffolds prepared by electrospinning with pore size diameter of 26.8±17.5 mm and thickness of 150±12 mm; lowest viscosity resulted in thickest fibers, largest interstitial spaces, thickest scaffolds, and best light transmission [65,66] Parylene-C Synthetic Biocompatible; nontoxic; good mechanical strength and biostability; semipermeable to macromolecules when thickness reduced to submicron range; mesh-supported submicron membrane; can withstand significant stretching force; epithelial-like morphology; tight intracellular junctions; correct polarization; well-developed microvilli; good cell adherence [112] A C C E P T E D M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…One study revealed that both ESCs and iPSCs were a good source of cells to generate RPE [35]. Another study revealed that iPSC-derived cells had a higher tendency for abnormal gene expression, which resulted in induction of the immune system [36,37]. Furthermore, it has been shown that ARPE-19 cells (from human RPE cell line primary cultures) can form a retinal like-tissue.…”
Section: Cellular Sources For Tementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, transplantation of RPE cells without repairing the structural damage caused in the BM during development of AMD does not lead to the therapeutic improvements sought in clinic [18]. To eliminate these complications, development of cell-sheets to transplant onto the native BM are being undertaken, with an aim that the cell-sheet will eventually secrete their own extracellular matrix (ECM) once reaching confluence [24][25][26]. This would restore the structural characteristics of the BM, thus supporting growth of the cell-sheet.…”
Section: Cell Suspensions and Cell Sheetsmentioning
confidence: 99%
“…Substrates include decellularized lens capsule, BM, Descemet's membrane or amniotic membrane, which have close composition and morphology to native tissue. Limited availability of donors and potential transmission of diseases, however, make it desirable to seek alternative substitutes [25,28]. Natural polymers such as collagen, fibrin or silk are biocompatible and have similar composition to natural ECM; but potential for inflammatory response and challenging mechanical properties have led to interest in synthetic biomaterials [25,29].…”
Section: Biomaterials For Dry Amdmentioning
confidence: 99%